Much ado about nothing? Recent labour market reforms in Germany ; a preliminary assessment - Gustav A. Horn; Camille Logeay; Katja Rietzler (Management Revue, 2008)
The article examines the macroeconomic effects of the recent labour market reforms in Germany. The reforms increased the downward pressure on wages and led to rising income inequality. Many German economists welcomed this effect, because they consider lower wages and higher wage dispersion major prerequisites for stronger employment growth. The theoretical analysis shows that a strategy of wage restraint might make sense in a small open economy, where exports play a dominating role. However, in a large and less open economy the negative effects of wage restraint on domestic demand are likely to outweigh the positive effects of enhanced competitiveness as could be observed in Germany in recent years. A comparison of the most recent two upswings confirms that the labour intensity of growth has not risen since the reforms. At the same time German wage restraint has contributed to increasing trade imbalances in the euro area.
Keywords: 650; Labour market reforms; wage restraint; employment; business cycle